2020
DOI: 10.1016/j.sjbs.2020.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy and germination in Dodonaea viscosa (Sapindaceae) from south-western Saudi Arabia

Abstract: Dodonaea viscosa (Sapindaceae) is widespread in the mountainous highlands of the southwestern part of Kingdom of Saudi Arabia, where it is a medicinally important species for the people in Saudi Arabia. Seeds of this species were collected from Mount Atharb in Al-Baha region, at an altitude of 2100 m. The aims of this study were to determine if the seeds of D. viscosa have physical dormancy (i.e. a water-impermeable seed coat) and, if so, what treatments would break dormancy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…The fact that concentrated sulphuric acid enhanced the germination of A. andongensis infers that the seed coat is a barrier to the germination of the species. This result is consistent with studies conducted on other plant species elsewhere which showed that concentrated sulphuric acid increased germination percentage (Filho et al, 2019;Al-Namazi et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The fact that concentrated sulphuric acid enhanced the germination of A. andongensis infers that the seed coat is a barrier to the germination of the species. This result is consistent with studies conducted on other plant species elsewhere which showed that concentrated sulphuric acid increased germination percentage (Filho et al, 2019;Al-Namazi et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…After the treatments, the seeds were soaked in running water for 24 h. The temperatures (TS) and times of immersion (CS and TS) were based on specific literature for the selected Conservation 2023, 3 282 species that report the use of temperatures between 65 • C and 100 • C [32,36,39,42,45,51,80]. For CS, sulfuric acid was used at different concentrations and immersion times for the same species [42,44,47,81]. Planting was carried out manually in Styrofoam seedbeds with alveoli of 5 cm in diameter and 20 cm deep, which were previously sterilized with a 2% solution of commercial sodium hypochlorite.…”
Section: Pre-germinative Treatmentsmentioning
confidence: 99%
“…After the treatments, the seeds were soaked in running water for 24 h. The temperatures (TS) and times of immersion (CS and TS) were based on specific literature for the selected species that report the use of temperatures between 65 °C and 100 °C [32,36,39,42,45,51,80]. For CS, sulfuric acid was used at different concentrations and immersion times for the same species [42,44,47,81].…”
Section: Pre-germinative Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations